A new and efficient methodology for olefin epoxidation catalyzed by supported cobalt nanoparticles - Rossi Fernández, Lucía Inés (2021)
A new heterogeneous catalytic system consisting of cobalt nanoparticles (CoNPs) supported on MgO and tert-butylhydroperoxide (TBHP) as oxidant is presented. This CoNPs@MgO/tBuOOH catalytic combination allowed the epoxidation of a variety of olefins with good to excellent yield and high selectivity. The catalyst preparation is simple and straightforward from commercially available starting materials and it could be recovered and reused maintaining unaltered its high activity.